PENGARUH LOW IMPACT EXERCISE TERHADAP TINGKAT STRESS LANSIA DI PANTI JOMPO TRESNA WERDHA ABDI BINJAI - Ayu Andini; Robitah Asfur; Rahmi Rahmi; Lita Septina Chaniago (Buletin Farmatera, 2026)
Abstract: Stress can affect various aspects of life, including physical, psychological and social changes. Ageing and declining health are often associated with mental health conditions such as depression. Increasing physical activity can help reduce stress and improve mental health, especially depression. Aerobic exercise can be beneficial for the elderly, as long as it has the right dosage and design. Aerobic exercise to improve the physical fitness of the elderly uses low-impact exercise. This study aims to determine the influence of exercise on the level of stress of the elderly in the nursing home of Tresna Werdha Abdi Binjai. Pre-experimental design with one group pretest-posttest design. Exercise is carried out for 8 weeks with an exercise duration of around 30 minutes, 3-5 times/week. Sampling was taken using the total sampling method. The data collection technique used the Perceived Stress Scale (PSS) questionnaire, which was taken before and after the exercise intervention. Based on the Wilcoxon Rank Sum Test output, it is known as a value of p=0.000 (p = 0.005), so it can be concluded that there is a significant difference between the pre-test and post-test results after the exercise intervention. There is an influence of low-impact exercise on the stress level of the elderly at the Tresna Werdha ABDI Binjai Nursing Home.